2019
DOI: 10.3389/fnana.2019.00039
|View full text |Cite
|
Sign up to set email alerts
|

Kcnab1 Is Expressed in Subplate Neurons With Unilateral Long-Range Inter-Areal Projections

Abstract: Subplate (SP) neurons are among the earliest-born neurons in the cerebral cortex and heterogeneous in terms of gene expression. SP neurons consist mainly of projection neurons, which begin to extend their axons to specific target areas very early during development. However, the relationships between axon projection and gene expression patterns of the SP neurons, and their remnant layer 6b (L6b) neurons, are largely unknown. In this study, we analyzed the corticocortical projections of L6b/SP neurons in the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 90 publications
(142 reference statements)
2
19
0
Order By: Relevance
“…Despite the central position of subplate neurons in orchestrating cortical connectivities, the molecular determinants of subplate wiring function remain largely elusive. Previous studies have focused on genes selectively expressed in subplate neurons Oeschger et al, 2012), which are found to mediate subplate neuron specification, migration, and axon development (Arai et al, 2019;Caviness, 1982;Han et al, 2011;Hevner et al, 2001;Kwan et al, 2008;Lai et al, 2008;Rakic et al, 2006;Ratie et al, 2019;Tiong et al, 2019). Here, by cell type-specific dissection of cortical Arid1a function, we uncover a surprisingly selective role for a ubiquitously-expressed chromatin remodeler in establishing the molecular identity and mediating the non-cell autonomous circuit wiring function of subplate neurons.…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations
“…Despite the central position of subplate neurons in orchestrating cortical connectivities, the molecular determinants of subplate wiring function remain largely elusive. Previous studies have focused on genes selectively expressed in subplate neurons Oeschger et al, 2012), which are found to mediate subplate neuron specification, migration, and axon development (Arai et al, 2019;Caviness, 1982;Han et al, 2011;Hevner et al, 2001;Kwan et al, 2008;Lai et al, 2008;Rakic et al, 2006;Ratie et al, 2019;Tiong et al, 2019). Here, by cell type-specific dissection of cortical Arid1a function, we uncover a surprisingly selective role for a ubiquitously-expressed chromatin remodeler in establishing the molecular identity and mediating the non-cell autonomous circuit wiring function of subplate neurons.…”
Section: Introductionmentioning
confidence: 82%
“…Molecular studies have largely focused on subplate-enriched genes Oeschger et al, 2012). Together, these studies have characterized molecular determinants of subplate neuron specification, migration, and axon development (Arai et al, 2019;Caviness, 1982;Han et al, 2011;Hevner et al, 2001;Kwan et al, 2008;Lai et al, 2008;Rakic et al, 2006;Ratie et al, 2019;Tiong et al, 2019), highlighting the complex genetic regulation required for subplate neuron development. The severe axon misrouting phenotypes of subplate ablation (Ghosh et al, 1990;Shatz, 1992, 1993), however, are not broadly recapitulated in these genetic mutants, precluding further mechanistic investigations into the circuit wiring functions of subplate neurons.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Expression of the Hsd11b1 gene across 1691 cells isolated from adult mouse S1 was analyzed using public single-cell RNA-seq data (Zeisel et al, 2015) as previously described (Tiong et al, 2019). The annotated expression data (equivalent to the raw data in Gene Expression Omnibus (GEO, https://www.ncbi.nlm.nih.gov/geo/) with the accession GSE60361 except for the cell type annotations) were obtained from the Linnarsson laboratory website (http://linna rsson lab.org/ cortex).…”
Section: Analysis Of Public Rnaseq Datamentioning
confidence: 99%